Deciphering S-Phase Protein Kinase 2 (Skp2) Mediated Regulation Of Telomerase Reverse Transcriptase (Tert) In Kasumi-1, T (8;21) Acute Myeloid Leukemia (Aml) Cell Line - Rosli, Nur Aliaa Arina (2023)
Acute myeloid leukemia (AML) is the most common acute leukemia in adults and is characterized by immature myeloid cell proliferation. S-Phase Protein Kinase 2 (SKP2) is a cell cycle regulator and shown to be overexpressed in AML patients. SKP2 potentiates to cause cell proliferation and division. Studies shown prolonged SKP2 knockdown suppress telomerase reverse transcriptase (TERT) expression in t(8;21) AML cells in vitro. Nevertheless, the molecular mechanism of TERT regulation by SKP2 remain unclear. Therefore, the aim of this study was to investigate the TERT mechanism by SKP2 in AML.SKP2 was suppressed in Kasumi-1 and THP-1 via siRNA mediated gene knockdown. In this study, TERT expression reduced at gene and protein level after SKP2 suppression in non t(8;21) AML cells. Accordingly, telomerase activity was also reduced in non t(8;21) AML cells. Result obtained show that c-Myc and FOXO3 did not play a direct role in SKP2 mediated TERT regulation in t(8;21) and non-t(8;21) AML cells at gene level. However, different pattern in c-Myc protein expression was observed in non t(8;21) AML cells. Another observation were made in t(8;21) AML cells after AML1/ETO knockdown where c-Myc was up-regulated at gene and protein level. Due to increase in c-Myc expression levels, chromatin immunoprecipitation (ChIP) was carried out and increased observed binding of c-Myc to the TERT promoter was observed after AML1/ETO down-regulation. However, c-Myc binding to the TERT promoter failed to induce TERT transcription in t(8;21) AML cells.Other proteins related to TERT mechanism xxii observed were Rb, E2F1 and CDKN1B. Hypophosphorylation of Rb was observed up-regulated in non t(8;21) AML cells after SKP2 knockdown yet no significant difference in E2F1 protein expression was observed. Accumulation of CDKN1B was markedly related with suppression of SKP2 in this studies.